Parent Assistance in The Use of Gadgets for Early Childhood Learning Process - Tri Rizki, Mohammad; Kustiono, Kustiono; Utanto, Yuli (Innovative Journal of Curriculum and Educational Technology, 2021)
This research is motivated by the increasing use of gadgets among children. This phenomenon encourages the role of parents to do mentoring on children in using gadgets, especially in the learning process. This research method uses qualitative descriptive approach with observation data collection techniques, documentation, questionnaires and interviews. The purpose of this study is to find out the involvement of parents in accompanying children when using gadgets in the learning process. The results of this study found the involvement of parents in accompanying children when using gadgets for the learning process is very necessary because with the involvement of parents children can be wise in the use of gadgets and more focused in learning. This research has implications on parents' knowledge about the assistance of gadget use for children aged 4 -5 years.